French diplomats and the military on Soviet Russia and the balance of power in Central-Eastern Europe in 1922 - I. E. Magadeev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The consolidation of the Soviet state in 1922 and the activities of Soviet diplomacy in the key international forums had a direct impact on the strategic situation in Europe. The eventual strengthening of Soviet Russia/the USSR was both a threat and an opportunity for France as one of the leading European powers of that period, which had obligations and interests in Central and Eastern Europe. The author aims to identify the main approaches of French diplomats and the military to a set of issues related to the possible development of Soviet Russia in 1922 and its place in the European balance of power. The study is based on a wide range of primary sources from the Diplomatic Archives of the Ministry of Europe and Foreign Affairs of France, the National Archives of France, the Historical Service of the Ministry of the Armed Forces of the Fifth Republic, as well as on recently published French diplomatic and military documents. The author concludes that the French elites had a rather ambiguous attitude towards the process and the first results of political consolidation and socio-economic development of the Soviet state. On the one hand, the formation of the USSR was an obvious manifestation of the growing Soviet power that somewhat diminished the hopes of French officials for the imminent fall of the Bolsheviks. At the same time, diplomats and the military both in Paris and on-site were often skeptical about the prospects for the development of the Soviet economy, noting the catastrophic consequences of hunger, economic and financial ruin. Moderate optimism about the opportunity to intensify trade and economic contacts with Soviet Russia as its economy recovers coexisted with pronounced pessimism. The French assessments of the military potential of the Soviet state were marked by the same ambivalence. The acknowledgement of the current limited capabilities of the Red Army and the Red Fleet was accompanied by the growing recognition that the basis of the military power of the Soviet state had not been undermined. All this could help Moscow improve its international stance in the future, which would inevitably affect the balance of power in Europe. Under these circumstances, the French elites debated the prospects for the ‘normalization’ of the Bolshevik regime and its incorporation into the Versailles order. The author argues that all these contradictory attitudes, views and assessments that surfaced in 1922 to a large extent predetermined the overall direction and specific content of the French policy towards the USSR in the following years.